Proses Terjadinya Konflik dalam Organisasi (Studi Kasus pada BUMD PT.X) - Setyawardani, Titis; ., Noermijati (Universitas Brawijaya, Indonesia, 2012)
Abstract: The aim of this research is to know the conflict process on BUMD (Regional-State Owned Enterprise) PT.X. Qualitative paradigm were used in this research with descriptive-explan writing technique and case study research design. Informants of this research are two ex-employees of BUMD PT.X based on the criteria determined by the researcher. Data analysis technique used in this research is content analysis. Data verification analyses used are construct validity, internal and external validity, and reliability. Thisresearch finds that the trigger factors of conflict in individual level are employee characteristics, reluctant culture, owe’s life, family values, and trust. The researcher also finds the trigger factors of conflict inorganizational level that are differentiation of employee capability, leadership style, individual vision difference, role ambiguity and responsibility of work, individual interest, and political interest. These trigger factors would create conflict perception on the employees and in turn would form the conflict. Theresult of conflict causes negative impact like high employee turnover, high conflict of interest, and high employees stress. Conclusion of this research is that conflict process occurs if there are trigger factors from individual level and organizational level as well. All of the trigger factors would shape perception of conflict in every one and would shape conflict. The impact of conflict would give negative outcomes.